Perluasan proses hierarki analisis kabur untuk keputusan multi-kriterium = Fuzzy Analytic Hierarchy Process-Extension for Multi-Criteria Decision - Tarmudi, Zamali; Md. Tap, Abu Osman (2011)
This paper discusses an extension of analytic hierarchy process which is adopted in fuzzy set theory for multi-criteria decision-making purposes. This method is utilised to overcome the fuzziness problem of the initial input data-sets using the concept of membership degree. The advantage of the proposed approach is applied in the hypothetical example of municipal solid waste decision-making problems. Based on the result, it shows that the approach is user friendly, able to minimise the initial input data-sets and very efficient in terms of problem solving approach. Besides that, it is beneficial as an alternative approach for solving multi-criteria decision-making problem.